Influence of stroke rate on core stability and rowing ergometer performance - Duchene, Y.; Simon, F.; Ertel, G.; Maciejewski, H.; Gauchard, G. C.; Mornieux, G. (ISBS - Conference Proceedings Archive (Konstanz), 2022)
The purpose of this study was to determine the effect of the stroke rate on rowing ergometer performance and more specifically on core stability. Twenty expert rowers performed 2 one-minute bouts at 20 and 34 strokes per minute, on a RowPerfect3 ergometer. The high stroke rate induced larger handle and trunk power production and delayed trunk extension during the drive phase. The analysis of co-activation ratios didn`t help the understanding of the differences induced by the stroke rate manipulation, but higher abdominal muscles activation was reported, that should help stabilizing the trunk, while power, along with stroke rate, increased. These findings could help trainers to better adapt the stroke rate to the different purposes, i.e. power or technique, of the training.